Standard specifications for transportation materials and methods of sampling and testing (American Association of State Highway and Transportation Officials, 2009)
The 29th Edition Materials Book contains 421 materials specifications and test methods commonly used in the construction of highway facilities. The AASHTO Provisional Standards is also included and contains an additional 42 provisional materials specifications and test methods.